The politics of international criminal law - Cullen, Holly; Kastner, Philipp 20./21.Jh; Richmond, Sean 1978- (Studies in International Criminal Law, 2021)
Bridge over troubled water : a semantic approach to purposes and goals in international criminal justice / Alexander Heinze -- The politics of international criminal justice : hegemony and humanity at the international criminal tribunal for the former Yugoslavia / Shannon Maree Torrens -- Constructing international criminal justice across time and space / Emma Palmer -- The office of the prosecutor : seeking justice or serving global imperialism? / Shannon Fyfe -- The law and politics of norm conflict : immunity versus accountability and the Case of Al-Bashir / Catherine Moore -- The lost Kenyan duel : the role of politics in the collapse of the international criminal court cases against Ruto and Kenyatta / Daniel M. Mburu -- Prosecution for the destruction of cultural property : significance of the Al Mahdi Trial / Lara Pratt -- Emotions in international criminal law : reckoning with the unknown / Josh Pallas -- The politics of reparations at the international criminal court / Miriam Cohen -- Private military security companies: addressing accountability : a suggested model for control / Pauline Collins -- Counterterrorism and national security : the domestic/international law interface / Vincent-Joël Proulx.